Home oral sugar salt solution using the "blue spoon"for acute infantile gastroenteritis - Abdul Latief Azis; Pitono Soeparto; Subijanto M. S.; Daniel Hardjadinata; Mien Kumiaijanto; Harsono Salino (Paediatrica Indonesiana, 1981)
Ninety-one children aged between 2 - 24 months (mean age of 10.07 Â± 5.29 months) with uncomplicated gastroenteritis were treated with home made oral sugar salt solution prepared by using the "Blue Spoon". They were randomly devided into 2 groups: those whose feedings were stopped and those who were still permitted 10 have their normal feedings while all oral electrolyte therapy. A total of four children (4.40%) developed dehydration following the administration of oral solution therapy. Vomiting was reversed in 24 out of 28 children following the administration of oral electrolyte solution. There were statistically no significant differences in failure rate e.g. the development of dehydration, vomiting and meteorism following oral electrolyte therapy between the two groups.Almost 01/ mothers (95.79%) followed the instructions as how to use the Blue Spoon and stated that it was a simple and a cheap means in preparing oral sugar electrolyte solution.